The multi-row displayed mathematics in the proof of the Fundamental Theorem had equations aligned on the equals signs via the & character. Sometimes you don't want that. Here is an example with some differential equations, with each equation centered and unnumbered,

\begin{gather*} {\mathcal L}(y')(s) = s {\mathcal L}(y)(s) - y(0) = s Y(s) - y(0)\\ {\mathcal L}(y'')(s) = s^2 {\mathcal L}(y)(s) - sy(0) - y'(0)= s^2 Y(s) - sy(0) - y'(0)\text{.} \end{gather*}

has a device where you can interrupt a sequence of equations with a small amout of text and preserve the equation alignment on either side. Here are two tests of that device, with aligned equations and non-aligned equations. Study the source to see use and differences. (The math does not make sense.)

Aligned and numbered first.

\begin{align} {\mathcal L}(y')(s) &= s {\mathcal L}(y)(s) - y(0) = s Y(s) - y(0)\tag{6.1}\\ {\mathcal L}(y'')(s) &= s^2 {\mathcal L}(y)(s) - sy(0) - y'(0)= s^2 Y(s) - sy(0) - y'(0).\tag{6.2}\\ \end{align}

And so it follows that,

\begin{align} {\mathcal L}(y')(s)^{++} &= s {\mathcal L}(y)(s) - y(0) = s Y(s) - y(0)\tag{6.3}\\ {\mathcal L}(y'')(s)^{5} &= s^2 {\mathcal L}(y)(s) - sy(0) - y'(0)= s^2 Y(s) - sy(0) - y'(0).\tag{6.4} \end{align}

Now with no numbers and no alignment. We include two cross-references in the intertext portion for testing.

\begin{gather*} {\mathcal L}(y')(s) = s {\mathcal L}(y)(s) - y(0) = s Y(s) - y(0)\\ {\mathcal L}(y'')(s) = s^2 {\mathcal L}(y)(s) - sy(0) - y'(0)= s^2 Y(s) - sy(0) - y'(0).\\ \end{gather*}

First an external reference to http://example.com and internal cross-reference to Corollary 4.1. And so it follows that,

\begin{gather*} {\mathcal L}(y')(s)^{++} = s {\mathcal L}(y)(s) - y(0) = s Y(s) - y(0)\\ {\mathcal L}(y'')(s)^{5} = s^2 {\mathcal L}(y)(s) - sy(0) - y'(0)= s^2 Y(s) - sy(0) - y'(0)\text{.} \end{gather*}

Tables can get quite complex. Simple ones are simpler, such as this example of numerical computations for Euler's method.